2009
DOI: 10.1002/jso.21344
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic role of myeloid cell leukemia‐1 protein (Mcl‐1) expression in human gastric cancer

Abstract: Mcl-1 is highly upregulated in gastric cancer and high Mcl-1 expression is correlated with a poor prognosis in gastric cancer patients. Thus, Mcl-1 can be utilized as an independent prognostic factor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
19
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 27 publications
5
19
0
Order By: Relevance
“…Melanoma cells upregulate the Mcl-1 level upon endoplasmic reticulum stress [29]. In gastric cancer, the Mcl-1 level was evaluated by an immunohistochemical technique, and the expression level of Mcl-1 was suggested as a prognostic marker [9,30]. In addition, the mechanisms by which gastric cancer cells upregulate Mcl-1 expression level were also evaluated recently.…”
Section: Discussionmentioning
confidence: 99%
“…Melanoma cells upregulate the Mcl-1 level upon endoplasmic reticulum stress [29]. In gastric cancer, the Mcl-1 level was evaluated by an immunohistochemical technique, and the expression level of Mcl-1 was suggested as a prognostic marker [9,30]. In addition, the mechanisms by which gastric cancer cells upregulate Mcl-1 expression level were also evaluated recently.…”
Section: Discussionmentioning
confidence: 99%
“…According to online database (https://www.cbligand.org/HTDocking/searchstruct.php) prediction, LH may have the possibility of interactions with MCL1 ( Fig S3A). As is reported in literature, we knew that MCL1 is highly expressed in gastric cancer, and the prognosis of patients with high expression of MCL1 is worse [32]. After treatment with different concentration of LH (10, 20 and 40 μM, DMSO was used as control) for 48 h, we found that MCL1, a critical anti-apoptotic protein from BCL2 family, was signi cantly decreased in a dose-dependent manner in both MKN-45 and SGC-7901 cells (Fig.…”
Section: Overexpression Of Mcl1 Restores Cells Proliferation and Decrmentioning
confidence: 63%
“…Besides, the MCL1 has recently been regarded as a promising target for cancer treatment [35,36]. In view of the previous reports, we knew that MCL1 is highly expressed in gastric cancer, and the prognosis of patients with high expression of MCL1 is worse [32]. In this study, LH was proved to cause cell cycle arrest at S phase and induced apoptosis in gastric cancer by inhibiting MCL1, which is consistent with the previous reports that MCL1 is involved in cell cycle by improving the stability of CDK2 protein [37].…”
Section: Discussionmentioning
confidence: 98%
“…It has been found in the past that chemotherapy and TRAIL, used simultaneously, can afford restoration of apoptosis in a large number of TRAIL‐ or chemoresistant tumour cells in vitro and in vivo (Gliniak and Le, ; Keane et al ., ; Walczak et al ., ; Cuello et al ., ; Lacour et al ., ; Ohtsuka et al ., ; Jin et al ., ; Shankar and Srivastava, ; Fiveash et al ., ), but these synergies were shown to critically rely on mitochondrial activation (von Haefen et al ., ; Nguyen et al ., ). Unfortunately, a large proportion of tumours, and not only haematological malignancies, spontaneously overexpress Bcl‐2 anti‐apoptotic family members or, to a lesser extent, display loss‐of‐function mutations of Bax (Meijerink et al ., ; Garcia et al ., ; Pepper et al ., ; Likui et al ., ) and in vitro studies demonstrate that simultaneous treatments are unable to overcome TRAIL resistance induced by a deficiency of Bax or the overexpression of Bcl‐2 (Fulda et al ., ; LeBlanc et al ., ; von Haefen et al ., ). Because recombinant TRAIL or moAb targeting TRAIL‐R1 or TRAIL‐R2 have been administered simultaneously starting from day 1 of each cycle with the chemotherapeutic compounds of interest, in most if not all clinical studies, the lack of efficacy of these combinations may be attributed to their inability to overcome the mitochondrial block (Ganten et al ., ; von Haefen et al ., ; Ndozangue‐Touriguine et al ., ; El Fajoui et al ., ; Morizot et al ., ; Jacquemin et al ., ).…”
Section: Study Design and Administration Of Trail And Derivatives: Lementioning
confidence: 98%